BEYOND FALLACIES: STRENGTHS AND QUALIFICATIONS FOR ENGLISH TEACHING PROFESSION IN INDONESIA - Sufyan, Agus; Hakim, Lukman; Jatmiko, M. Anang; Ustufiarrizqi, Ustufiarrizqi (University of Kuningan, 2024)
Proposing the idea of perception toward native English-speaking teachers (NESTs) and non-native English-speaking teachers (non-NESTs), this research was motivated by the historical changes from the ‘fallacies’ in finding the most suitable English teachers between the two categories to discussing their potential if those teachers collaborated in team teaching. This study aimed to reveal a) the top three language skills pre-service English teachers perceived to improve if taught by either NESTs or Indonesian English teachers and b) the priority list of qualifications to meet by them. The quantitative findings from a close-ended questionnaire involving 186 pre-service English teachers in the Department of English Education at an Indonesian university indicated that the respondents tend to view NESTs as good models to teach oral-aural skills such as listening, pronunciation, and speaking. On the other hand, Indonesian English teachers could better-supporting students in teaching written skills such as grammar, vocabulary, and writing skills, which are more related to accuracy and language features. For the second objective, our results indicated that our respondents agreed that the English teaching profession should have fair treatment. Both NESTs and Indonesian English teachers are required to have relevant academic qualifications, and teaching experiences were viewed.